Blight of some Commercial Species of Mentha in Himachal Pradesh - Sharma, A. D.; Munjal, R. L. (Indian Forester, 1978)
Rhizoctonia solani caused severe blight of three commercial species of Mentha. In pathogenicity tests, in addition to Mentha citrata, M.epicata and M. piperita, the fungus also infected M.sylvesiris. Symptoms of the disease and morphology of the pathogen has been described.